PENGARUH KOMPETENSI DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA PEGAWAI PADA KANTOR KECAMATAN CIPUTAT TANGERANG SELATAN - Hibatul Haqqi, Muhammad; Nariah (Journal of Research and Publication Innovation, 2024)
The purpose of this study was to determine the effect of competence and work environment on employee performance either partially or simultaneously at Ciputat sub-district office, South Tangerang. This research method uses quantitative methods with an associative causal approach.. Data collection methods used are primary data and secondary data. The sampling technique in this study used the Jenuh technique, as many as 65 respondents. Data analysis using SPSS version 26 program. The analytical techniques used are validity test, reliability test, classic assumption test, normality test, multicollinearity test, heteroscedasticity test, auto correlation test, simple linear regression analysis, multiple linear regression analysis, correlation coefficient test, coefficient of determination test and hypothesis testing. Partial hypothesis testing of competence variable (X1) obtained tcount > ttable (4,900 > 1.670) and a significance value of 0.000 <0.05. This means that placement (X1) has a significant effect on employee performance (Y). The partial hypothesis test for the work environment variable (X2) obtained a value of tcount > ttable (5.651 > 1,669) and a significance value of 0.000 <0.05. This means that the training (X2) has a significant effect on employee performance (Y). The multiple linear regression equation obtained is Y = 12.258 + 0.296X1 – 0.429X2. Simultaneous hypothesis testing obtained fcount > fable (18,100 > 3,15) and a significance value of 0.000 < 0.05. So it can be concluded that placement (X1) and training (X2) have a significant simultaneous effect on employee performance (Y). Determination obtained R Square of 0,369, meaning that the variables of competence and work environment together have an influence contribution of 36,9% on employee performance. While the remaining 63,1% is influenced by other factors not examined in this study.